Vision Pastoralist for Youth 2026 - Future of pastoralism in the face of climate change: Consultation outcome document, Kenya, 27-29 September 2022 - Sarpong, Linda; Agida, Christopher A.; Nashipae, Charity; Njora, Stephen; Tarimo, Doreen; Divine, N.T.F. (Climate Smart Agriculture Youth Network Global, 2022)
Traditional pastoralism is a unique and resilient system for ensuring adaptation to climate change. This adaptation is particularly important to deal with a dynamic process of unpredictable climate variability and permanent human interactions in dryland ecosystems in Africa. It is considered of fundamental importance to ensure the application of innovative techniques and mechanisms to deal with these changes, and that these technologies are strategically integrated into community social structures and resource management value systems. Unfortunately, prolonged marginalization and damaging external interventions to pastoral livelihoods are causing great vulnerability to pastoral populations in the region. There are many threats that pas-toral systems face on a daily basis, such as population growth, poor governance, the development of conflicting economic activities, and the reduction of grasslands and fertile lands for communal use and all this is exacerbated by climate change. Pastoralism, in addition to being a resilient production system, maintains biodiversity and landscapes. Recognizing the need to promote pastoralism and adaptation to climate change in the Region, CSAYN, ILRI, CGIAR and PROCASUR have partnered to conduct a consultation on pastoralism and climate change with young African members of the CSAYN to share knowledge and experiences on successful adaptation strategies in the sector and exchange information on bad practices and opportunities.